Butterfly Diversity in Mahadare Conservation Reserve, Satara (MS), Western Ghats: A Synoptic Checklist - Sutar, Shweta R.; Bhoite, Sunil H.; Pawar, Pratima A.; Bendre, Neha N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The Dare Khurd Mahadare Conservation Reserve (MCR) a forest situated near Satara City in the Mahadare village, is a vital part of Northern Western Ghats. The landscape of this reserve comprises grassland, semi-evergreen, and deciduous forest creating an ecotone. The diverse floral composition of the forest provides an ideal habitat for many butterfly species, which led to the documentation of 184 butterfly species in this study area, marking the first comprehensive sampling of the butterfly fauna in the reserve. A checklist has been compiled, following a thorough investigation of butterfly diversity within the reserve and its surrounding areas. The checklist comprises 184 butterfly species, from 112 genera and six families notably, out of the 364-butterfly species documented in the Western Ghats region.